Genetics and clinical implications of SPINK1 in the pancreatitis continuum and pancreatic cancer - Qi-Wen Wang; Wen-Bin Zou; Emmanuelle Masson; Claude Férec; Zhuan Liao; Jian-Min Chen (Human Genomics)
Abstract Serine peptidase inhibitor, Kazal type 1 (SPINK1), a 56-amino-acid protein in its mature form, was among the first pancreatic enzymes to be extensively characterized biochemically and functionally. Synthesized primarily in pancreatic acinar cells and traditionally known as pancreatic secretory trypsin inhibitor, SPINK1 protects the pancreas by inhibiting prematurely activated trypsin. Since 2000, interest in SPINK1 has resurged following the discovery of genetic variants linked to chronic pancreatitis (CP). This review provides a historical overview of SPINK1's discovery, function, and gene structure before examining key genetic findings. We highlight three variants with well-characterized pathogenic mechanisms: c.-4141G > T, a causative enhancer variant linked to the extensively studied p.Asn34Ser (c.101A > G), which disrupts a PTF1L-binding site within an evolutionarily conserved HNF1A-PTF1L cis-regulatory module; c.194 + 2T > C, a canonical 5′ splice site GT > GC variant that retains 10% of wild-type transcript production; and an Alu insertion in the 3′-untranslated region, which causes complete loss of function by forming extended double-stranded RNA structures with pre-existing Alu elements in deep intronic regions. We emphasize the integration of a full-length gene splicing assay (FLGSA) with SpliceAI’s predictive capabilities, establishing SPINK1 the first disease gene for which the splicing impact of all possible coding variants was prospectively determined. Findings from both mouse models and genetic association studies support the sentinel acute pancreatitis event (SAPE) model, which explains the progression from acute pancreatitis to CP. Additionally, SPINK1 variants may contribute to an increased risk of pancreatic ductal adenocarcinoma (PDAC). Finally, we discuss the therapeutic potential of SPINK1, particularly through adeno-associated virus type 8 (AAV8)-mediated overexpression of SPINK1 as a strategy for treating and preventing pancreatitis, and highlight key areas for future research.